2017
DOI: 10.21917/ijms.2017.0068
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Demographic Variables on the Employee Engagement - An Analysis

Abstract: Employees play a pivotal role in the success of every organization. They help to achieve organizational objectives. Various studies indicate that a highly-engaged employee can help the organization to respond to the changes in environment, competition, and changing workforce. The extent to which an employee believes in the mission and purpose of an organization and demonstrates commitment through their action and their attitude towards their employer is employee engagement. The aim of this paper is to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In sectors like manufacturing, they need a good style such as transactional, laissez-faire style of leadership. Empirical evidences have shown that leadership behaviours have an influence on employee performance (Lianying et al, 2018;Marcus & Namitha, 2017;Maria & Álvaro, 2019). This suggests leaders that are strong overshadow weak leaders, also transformational style of leadership brings about greater performance than transactional style of leadership.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In sectors like manufacturing, they need a good style such as transactional, laissez-faire style of leadership. Empirical evidences have shown that leadership behaviours have an influence on employee performance (Lianying et al, 2018;Marcus & Namitha, 2017;Maria & Álvaro, 2019). This suggests leaders that are strong overshadow weak leaders, also transformational style of leadership brings about greater performance than transactional style of leadership.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire items were modified and adopted standard questions based on items from the validated survey works of previous scholars in similar subject areas. The leadership dimensions' items were from (Ana et al, 2014;Anastasia, 2018;Deribe, 2016;Lianying et al, 2018) and employee engagement were also adapted from previous studies (Khan et al, 2016;Marcus & Namitha, 2017;Sasmita & Manoj, 2018;Sunita et al, 2015). Job performance measurements were adopted and adapted from (Isabel et al, 2019;Olanipekun et al, 2015;Simbo et al, 2012;Thomas, 2017;Zohra et al, 2018).…”
Section: Data Measurement and Analysis Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Christen et al (2006) noted that job performance increased with both effort and ability. Previous research suggests that among the various variables influencing job performance; employee engagement and organizational culture play an important role (Carrell and Elbert, 1974;K onya et al, 2016;Marcus and Gopinath, 2017;Kalia and Bhardwaj, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…To overcome these problems, different factors that affect the job performance of hotel employees such as job characteristics, work environment, individual factors, esteem, leadership, among others were identified (Dodd et al, 2015;Bakker et al, 2012;Chughtai and Buckley, 2010). Previous research studies suggest that among all the various factors affecting the job performance of employees, widely contributing factors are demographic variables, organizational variables, employee engagement and organizational culture (Carrell and Elbert, 1974;Konya et al, 2016;Marcus and Gopinath, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%